(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the activities of the prosecutor’s office in the field of protection of human rights and the main legislative acts regulating these activities. The author reflects on the historical formation of the Institute of Public Prosecutions, its constitutional status and its role in ensuring human rights. The article also covers the current laws of the Republic of Uzbekistan, the norms of international law and the mechanisms for the expansion of the powers of the prosecutor’s office and the effective protection of human rights within the framework of judicial reform. Through analyzes, current problems in this area and ways to solve them have been proposed.